Capacity of materials with wearproof coverages - Гладкий, Я.М.; Маковкін, О.М. (Problems of Tribology, 2014)
In work, influencing of coverages is explored, got different technologies on wearproof properties of instrumental steels. Are got to dependence of the line tearing down on the way of friction and modes of operations, close to the real process of cutting of metals.